REAL ESTATE IN INDIA – IS ITS FUTURE AT STAKE? - Srivastava, Preeti (International Journal of Psychosocial Rehabilitation, 2020)
This paper shall be focusing on Real Estate in India which is a globally recognized sector. As we all are aware of the current scenario of real estate sector that its going towards downfall to as much as 50% in few cities. People now are bit resistive towards investing in it. They are expecting more downfall to come. Though they want to invest for the reason that land is a scarce resource so in the long term it shall be valuable but will they be fooled if they buy now – that’s the fear! This paper shall be analyzing and focusing towards the outlook of a common man that how do they think and what are their perceptions towards this sector. This we shall be doing with the help of simple graphical structures. Though no one can deny the fact that this sector has been one of the ultimate places to park money over a period of time of every earning person. Everyone on Earth earns with a dream to have their own land and building someday, when all the earners shall participate in the estate purchase how can downfall even touch this sector- Impossible! So, the data is revealing an opposite figure as compared to the general market sentiments of Indians. This is what this paper is about to find out the future of this real estate sector- where its heading and is it future is at stake? or is it still a safe and lured investment from the point of view of a common man.